Biocompatibility of cleaning agents for ocular prostheses - Andreotti, Agda Marobo [UNESP] (2021)
This study aimed to access the cytotoxicity, on the human conjunctival cell line, of different agents (neutral soap, 4% chlorhexidine, Efferdent effervescent tablets, 1% triclosan, and citronella essential oil) used for cleaning ocular prosthesis. Human conjunctival cell line was cultivated on acrylic resin specimens and the cytotoxicity of the studies cleaning agents was evaluated by MTT, Neutral Red, and RT-PCR (Real-time reverse transcription polymerase chain reaction) for the gene expression of type IV collagen, transforming growth factor β, myeloid cell leukemia sequence 1, matrix metalloproteinase 9, and caspases 3 and 9. Data were submitted to the two-way analysis of variance (ANOVA) and Bonferroni (p<0.05) tests. All cleaning agents showed biocompatibility for the human conjunctival cells. This, immersion in 4% chlorhexidine, effervescent tablets, and 1% triclosan could be the best protocols indicated for ocular prosthesis cleaning due to their biocompatibility.